2010
DOI: 10.1108/17465261011045124
|View full text |Cite
|
Sign up to set email alerts
|

Building organizational trust in a low‐trust societal context

Abstract: PurposeThe purpose of the paper is to explore the interrelations between organizational trust and ethics management tools as well as ethical organizational practices in a post‐socialist context.Design/methodology/approachA conceptual framework of the interrelations among organizational trust, ethics management tools and ethical organizational practices is reasoned and the interrelations among the variables are explored using quantitative methods of data analysis. The method of data gathering is a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 53 publications
1
45
0
Order By: Relevance
“…In this respect, organisation's ethics code may be signalling even to new employees that the organisation may be worth trusting and induce trust. The studies by Pu tait et al (2010a;2010b) demonstrate that employees of multinational organisations which are reputable as employers and have corporate social responsibility programmes and/or ethics codes, developed affective trust first and later rationalised it. However, in public organisations, ethical culture of an organisation could induce cognitive trust first as these organisations are much more bureaucratic compared to private organisations; their activities and management practices are much more standardized and therefore ethical culture of an organisation may be perceived as a regulatory mechanism, which appeals to rational judgement rather than emotions.…”
Section: Ethical Culture Of An Organisation and Organisational Trustmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, organisation's ethics code may be signalling even to new employees that the organisation may be worth trusting and induce trust. The studies by Pu tait et al (2010a;2010b) demonstrate that employees of multinational organisations which are reputable as employers and have corporate social responsibility programmes and/or ethics codes, developed affective trust first and later rationalised it. However, in public organisations, ethical culture of an organisation could induce cognitive trust first as these organisations are much more bureaucratic compared to private organisations; their activities and management practices are much more standardized and therefore ethical culture of an organisation may be perceived as a regulatory mechanism, which appeals to rational judgement rather than emotions.…”
Section: Ethical Culture Of An Organisation and Organisational Trustmentioning
confidence: 99%
“…Prior research in this context (Pu tait et al, 2010a) found organisational trust to depend on human resource management (HRM) practices that are based on the principles of fairness and justice as well as employee participation in decisionmaking and open communication. Another study on the effects of ethics management tools such as ethics codes, ethics training, ethics auditing etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Original article 4 Does it pay to be ethical? Examining the relationship between organisations´ ethical culture and innovativeness minimum level of responsibility (Carroll, 1991) but these formal standards cannot in themselves ensure ethical behaviour (Pučėtaitė et al, 2010). This being the case, the organisation's own culture has an important role to play in creating and improving ethical behaviour and in concretising the ethical values of the organisation (Sinclair 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Legal regulations define a minimum level of responsibilities for which organisations can be held accountable (Carroll, 1991) but they are limited as a guide to ethical behaviour, for example, due to their backward orientation. Value statements and codes of conduct for their part are often rather general expressions and could even be considered quite meaningless declarations unconnected to organisational practices (Pučėtaitė et al, 2010). Therefore the potential of an organisation's own culture for creating and improving ethics is important (Sinclair, 1993).…”
Section: Introductionmentioning
confidence: 99%